Prevention and Treatment of Venous Thromboembolism in Pregnancy: Pencegahan dan Tatalaksana Tromboemboli Vena pada Kehamilan - Erna Suparman (Indonesian Socety of Obstetrics and Gynecology, 2022)
Abstract Objective: To determine prevention and treatment of venous thromboembolism in pregnancy Methode: Literature Review Results: The diagnosis of TEV, both deep vein thrombosis (DVT) and pulmonary embolism (PE) was clinical and confirmed by imaging. D-dimers commonly used in the non-pregnant population are less useful in pregnant women. Prevention needs to be done by assessing the risk of TEV in pregnant women and giving thrombophylaxis according to risk. Treatment of TEV in pregnant women mainly uses heparin, either unfractionated heparin (UFH) or low molecular weight heparin (LMWH). Conclusion: The ASH recommends the use of LMWH compared with UFH for the management of acute VTE in pregnancy, in once-daily or divided doses. The recommended method of delivery for pregnant women receiving anticoagulant therapy should be planned delivery Key word : vein thromboemboli, deep vein thrombosis, pulmonary embolism, pregnancy Abstrak Tujuan: mengetahui bagaimana pencegahan dan tatalaksana tromboemboli vena pada kehamilan Metode: Kajian Pusataka Hasil: Diagnosis TEV, baik Deep vein thrombosis (DVT) dan pulmonary embolism (PE) berdasarkan klinis dan dikonfirmasi dengan pencitraan. D-dimer yang biasa digunakan pada populasi non-hamil kurang berguna pada ibu hamil. Pencegahan perlu dilakukan dengan menilai risiko TEV pada ibu hamil dan memberikan trombofilaksis sesuai dengan risiko. Tatalaksana TEV pada ibu hamil terutama menggunakan heparin, baik unfractionated heparin (UFH) maupun low molecular weight heparin (LMWH). Kesimpulan: ASH merekomendasikan penggunaan LMWH dibandingkan dengan UFH untuk pengelolaan VTE akut pada kehamilan, dalam dosis sekali sehari atau terbagi. Metode persalinan yang direkomendasikan untuk ibu hamil yang menerima terapi antikoagulan harus direncanakan persalinan Kata kunci : tromboemboli vena, deep vein thrombosis, pulmonary embolism, kehamilan